Eficiencia de un destilador solar, adaptando colector y reflector solar - Guerrero Cornejo, Nathaly Marilyn (2020)
The objective of the study was to evaluate the efficiency of a solar still, adapting a solar collector and reflector for the distillation of saline water. These distillers were implemented in Bahía de Caráquez city in La Acuarela 2 neighborhood, taking into account that solar radiation has a higher incidence in the coastal areas of Ecuador. The climatic data of the PUCE-Bahía meteorological station, area where the distillation systems were implemented, were analyzed; the climatic data analyzed were: temperature, heliophany, precipitation and solar declination, as well as pre and post distillation analyzes to be compared with the legislature of Book 1 of the TULSMA. Likewise, the choice and design of the solar stills, collector and solar reflector was made, the most used material was glass for its functionality and economy. On the other hand, a 30-day monitoring of the distillation process was carried out to subsequently carry out the tabulation through the Excel 2013 program, where the ambient temperatures, internal temperatures of the two stills were taken into account, as well as the volume of distilled water daily. Finally, it was possible to determine that the distillation processes serve to reduce: the fecal load, total dissolved solids, pH, among others, allowing them to be within the maximum permissible limits for waters for human consumption and domestic use, also boosted with efficiency 25% average of the distiller adapted based on a conventional distiller.